Biomass Position for Renewable Energies: Main Ways of Energetic Valorization - A. Zoulalian (Journal of Applied Fluid Mechanics, 2010)
The growth of some pollutants such as carbon dioxide, methane, etc… in the atmosphere induces the rise of temperature on the earth and the rarefaction of fossil energies (coal, oil, natural gas, …) and encourages the most industrial and developed countries, to promote renewable energies. Among these energies, biomass represents nowadays the main power supply (more than 50%). If the biomass has allowed since the antiquity the production of heat, the recent researches are focused on the simultaneous production of electricity and fuels under different physic forms (solid, liquid or gas) such as methane and hydrogen. The objective of the manuscript is to precise the different energetic valorizations of biomass.